Chirurgie beim M. Crohn = Surgery in Crohn’s disease - Horisberger, Karoline; Kienle, Peter (Der Chirurg, 2015)
Surgical treatment is primarily used to treat complications of Crohn’s disease but also to improve the quality of life. An adequate preoperative preparation including improvement of the nutritional status, weaning off or stopping immunosuppressive medication and preoperative drainage of abscesses can decrease the complication rate. With the exception of when neoplasia is present, bowel-sparing techniques (e. g. strictureplasty and limited resection) are now standard, which has resulted in a low risk of short bowel syndrome. The laparoscopic approach is possible for most indications even in the case of recurrent disease, in primary ileocecal resection the laparoscopic approach has been shown to be superior to the open approach. None of the available techniques for anastomotic reconstruction of the bowels has been shown to be superior. A drainage seton is a good option to retain the quality of life in complex fistulas and reconstructive repair should only be considered when the rectum is free from inflammation.